2013
DOI: 10.1021/pr4010579
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Analysis Identifies d-Alanine-d-Alanine Ligase as the Primary Lethal Target of d-Cycloserine in Mycobacteria

Abstract: D-cycloserine is an effective second line antibiotic used as a last resort to treat multi (MDR)- and extensively (XDR)- drug resistant strains of Mycobacterium tuberculosis. D-cycloserine interferes with the formation of peptidoglycan biosynthesis by competitive inhibition of Alanine racemase (Alr) and D-Alanine-D-alanine ligase (Ddl). Although, the two enzymes are known to be inhibited, the in vivo lethal target is still unknown. Our NMR metabolomics work has revealed that Ddl is the primary target of DCS, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 56 publications
3
74
0
Order By: Relevance
“…Cycloserine inhibits several enzymes within the peptidoglycan biosynthesis pathways, particularly D-alanine-D-alanine ligase, a main enzyme of this pathway (63). These methods can be used to study the growth and replication of the organisms.…”
Section: Metabolomics As Predictive Biomarkersmentioning
confidence: 99%
“…Cycloserine inhibits several enzymes within the peptidoglycan biosynthesis pathways, particularly D-alanine-D-alanine ligase, a main enzyme of this pathway (63). These methods can be used to study the growth and replication of the organisms.…”
Section: Metabolomics As Predictive Biomarkersmentioning
confidence: 99%
“…Absolute concentrations can then be calculated, provided that an internal standard of known concentration has been added to the sample. HSQC 0 has been successfully applied by Halouska et al to better understand the impact of D-cycloserine on mycobacteria [18]. This strategy is however limited to the HSQC sequence, and its overall sensitivity per unit of time is relatively limited since three spectra must be recorded in fully relaxed conditions for each sample.…”
Section: Accurate Quantitative Metabolomics By 2d Nmrmentioning
confidence: 99%
“…It is bacteriostatic in action; main mechanism of action being inhibition of cell wall synthesis by competitive inhibition of alanine racemase and d-alanine-d-alanine ligase [37]. Neuropsychiatric side effects of cycloserine are mediated by NMDA receptors; they are usually dose and concentration dependent [38] A systematic review on treatment outcome of MDR-TB in children reported adverse events related to cycloserine in only 6 out of 182 children [39].…”
Section: What Regimen To Start?mentioning
confidence: 99%